“THE CORRUPTION OF THE AMERICAN DREAM” IN THE NOVEL ”THE AMERICAN TRAGEDY” BY THEODORE DREISER - Farmanov Gayrat, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: In An American Tragedy by Theodore Dreiser, the theme of the corruption of the American Dream is central to the narrative and its exploration of social ambition, personal failure, and moral decay. The novel follows the life of Clyde Griffiths, a young man who dreams of achieving wealth, status, and success in American society. However, his quest to reach the upper echelons of society ultimately leads him to moral corruption, tragedy, and, ultimately, ruin.